Effects of computer-assisted glosses on EFL learners' vocabulary acquisition and reading comprehension in three learning conditions. (April 2017) - Khezrlou, Sima; Ellis, Rod; Sadeghi, Karim
Abstract: This study investigated the effectiveness of explicit, incidental, and intentional learning conditions on vocabulary acquisition and reading comprehension in a multimedia environment. A total of 99 university learners of English as a foreign language (EFL) were asked to read computer-based reading texts including text-picture-audio glosses of the target lexical items. In the explicit learning condition, learners received explicit instruction about the target lexical items before reading (EIG). In the intentional condition, learners were instructed to check the multimedia glosses while reading the texts (+IG) whereas in the incidental condition, they did not receive such instruction (-IG). Reading comprehension was measured through multiple-choice and written recall tests and vocabulary acquisition was measured through the vocabulary knowledge scale (VKS) and word recognition test (WRT). The results indicated that there were vocabulary gains for all the groups regardless of the learning conditions. While the EIG and +IG achieved a similar VKS performance, the EIG made greater gains of target vocabulary in the WRT. In addition, EIG was the only condition to maintain a long-term knowledge of the learned words. For reading comprehension, results varied according to the tests, with the +IG faring better in multiple-choice test and EIG achieving a higher written recall.